1991
DOI: 10.1007/bf02503457
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia after nissen fundoplication

Abstract: Nissen fundoplication is a commonly used antireflux operation. After this operation symptoms such as dysphagia, inability to belch and vomit, and gas bloating are frequently reported in the literature. In 32 patients who underwent Nissen fundoplication 3.5-18 years ago, postprocedure dysphagia was studied using conventional manometry and 24 h ambulatory pressure and pH recording. Our study indicates that dysphagia tends to decrease after surgery. Neither conventional nor ambulatory pressure recording revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Even if there had been any patients with dysphagia, an ambulatory motility study would not reveal the diagnosis. In a previous study no motility abnormalities were found as a causal factor for dysphagia in post-Nissen patients (11). In our study healing of oesophagitis was proved by endos-copy, and because all patients received maintenance treatment, none of them experienced reflux symptoms at the time of operation.…”
Section: Discussionsupporting
confidence: 48%
“…Even if there had been any patients with dysphagia, an ambulatory motility study would not reveal the diagnosis. In a previous study no motility abnormalities were found as a causal factor for dysphagia in post-Nissen patients (11). In our study healing of oesophagitis was proved by endos-copy, and because all patients received maintenance treatment, none of them experienced reflux symptoms at the time of operation.…”
Section: Discussionsupporting
confidence: 48%
“…Delayed gastric emptying is a known predisposing factor for wrap failure [20,21]. Failed fundoplication can be a challenging problem and it is better avoided.…”
Section: Surgical Managementmentioning
confidence: 99%
“…11,12 Increased basal and nadir LOS pressure postfundoplication is frequently associated with impaired oesophageal bolus clear-ance 11 and dysphagia. 13,14 However, a recent study of non-operated patients undergoing combined manometry and impedance measurement reported that none of the patients with isolated incomplete LOS relaxation had abnormal bolus clearance. 15 Whilst current evidence suggests that nadir LOS pressure may influence oesophageal bolus clearance, its impact on the relationship between pressure wave amplitude and oesophageal bolus clearance remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of nadir LOS pressure on oesophageal clearance is best evidenced through conditions such as postfundoplication dysphagia from tight wrap 11,12 . Increased basal and nadir LOS pressure postfundoplication is frequently associated with impaired oesophageal bolus clearance 11 and dysphagia 13,14 . However, a recent study of non‐operated patients undergoing combined manometry and impedance measurement reported that none of the patients with isolated incomplete LOS relaxation had abnormal bolus clearance 15 …”
Section: Introductionmentioning
confidence: 99%